Neonatal Selenium Deficiency Decreases Selenoproteins in the Lung and Impairs Pulmonary Alveolar Development - Laura G. Sherlock; William C. McCarthy; Maya R. Grayck; Mack Solar; Andres Hernandez; Lijun Zheng; Cassidy Delaney; Trent E. Tipple; Clyde J. Wright; Eva S. Nozik (Antioxidants, 2022)
Decreased selenium (Se) levels during childhood and infancy are associated with worse respiratory health. Se is biologically active after incorporation into Se-containing antioxidant enzymes (AOE) and proteins. It is unknown how decreased maternal Se during pregnancy and lactation impacts neonatal pulmonary selenoproteins, growth, and lung development. Using a model of neonatal Se deficiency that limits Se intake to the dam during pregnancy and lactation, we evaluated which neonatal pulmonary selenoproteins are decreased in both the saccular (postnatal day 0, P0) and early alveolar (postnatal day 7, P7) stages of lung development. We found that Se deficient (SeD) pups weigh less and exhibit impaired alveolar development compared to Se sufficient (SeS) pups at P7. The activity levels of glutathione peroxidase (GPx) and thioredoxin reductase (Txnrd) were decreased at P0 and P7 in SeD lungs compared to SeS lungs. Protein content of GPx1, GPx3 and Txnrd1 were decreased in SeD lungs at P0 and P7, whereas Txnrd2 content was unaltered compared to SeS controls. The expression of NRF-2 dependent genes and several non-Se containing AOE were similar between SeS and SeD lungs. SeD lungs exhibited a decrease in selenoprotein N, an endoplasmic reticulum protein implicated in alveolar development, at both time points. We conclude that exposure to Se deficiency during pregnancy and lactation impairs weight gain and lung growth in offspring. Our data identify multiple selenoproteins in the neonatal lung that are vulnerable to decreased Se intake, which may impact oxidative stress and cell signaling under physiologic conditions as well as after oxidative stressors.